MEMPERSIAPKAN SDM (GENERASI MILENIAL YANG UNGGUL DALAM BERWIRAUSAHA UNTUK MEGHADAPI REVOLUSI INDUSTRI 4.0 DAN 5.0) - A.Nur Asri Ainun (Career Development Center Division at Amkop Business School, 2023)
One of the efforts made by the government to reduce the growth of unemployment in Indonesia is to encourage the younger generation to become entrepreneurs. Becoming an entrepreneur is one way for someone to work and pursue a career for their life in the future. Entrepreneurship can also open new jobs for people who need or are looking for a job, besides that it can help the government's task of reducing unemployment growth in this country. Especially in facing industry 4.0 and the era of society 5.0, the younger generation should be able to hone their skills.